Contenido de compuestos fenólicos y potencial antioxidante en extractos de Prunus rotunda - Freitas Babilonia, Keila Kandi (2025)
Objective: To quantify the phenolic compound content and evaluate the antioxidant potential in extracts from the leaves and bark of Prunus rotunda. Methodology: Total phenols, flavonoids, anthocyanins, and catechins in the leaf and bark extracts of P. rotunda were quantified using UV-Visible spectroscopy. Antioxidant activity was evaluated using the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method, calculating the inhibition percentage at concentrations of 1, 10, and 15 mg/mL. Results: The bark exhibited higher concentrations of total phenols (19118.74 mg/100g), flavonoids (35.596 mg/100g), and anthocyanins (24.604 mg/100g) compared to the leaves (13153.05 mg/100g, 25.680 mg/100g, and 19.819 mg/100g, respectively). However, the leaves showed a slightly higher content of catechins (0.073 mg/100g vs. 0.066 mg/100g in the bark). In terms of antioxidant activity, the bark displayed a higher inhibition percentage at lower concentrations, achieving an IC50=0.54 mg/mL, while the leaves only reached comparable inhibition levels at higher concentrations, with an IC50=8.17 mg/mL. Conclusion: The bark of P. rotunda stands out as a rich source of phenolic compounds with remarkable antioxidant activity.